Obesity as Contemporary Metaphor: a “Healthy Crusade” on Behalf of Consumption and Risk - Gomes, Ivan Marcelo (Movimento, 2006)
This essay tries an interpretation of contemporary society through the obesity metaphor. We presented it linked with the vagabond’s metaphor formulated by Zygmunt Bauman. The obesity and the obese are analyzed as an ambivalent phenomenon, that therefore contributes for understanding certain forms of actual social exclusion at the present time. The concepts of society of risk by Ulrich Beck and of liquid modernity by Zygmunt Bauman are theoretical foundation for this reflection.